Narrating Cultural Citizenship: Oral Histories of First-Generation College Students of Mexican Origin - Benmayor, Rina (Social justice, 2002)
Part of a special issue on new pedagogies for social change. The writer proposes a cultural framework for interpreting the experiences of first-generation college students of Mexican origin so that educational institutions and faculty can understand their aspirations, commitment, and what advantages they bring to the classroom and the larger society. She contends that the narration of cultural citizenship can help these students to negotiate and interconnect to multiple allegiances, without having to cut their traditional ties or even limit their aspirations, while at the same time challenging the institutions and ideologies connected to college education.